Neuroinflammation Upregulated Neuronal Toll-Like Receptors 2 and 4 to Drive Synucleinopathy in Neurodegeneration - Chung, Lucia Yi-Ru; Lin, Yi-Ting; Liu, Chi; Tai, Yi-Cheng; Lin, Han-Yi; Lin, Chin-Hsien; Chen, Ching-Chow (Frontiers in Pharmacology, 2022)
BACKGROUND: Parkinson’s disease (PD) is characterized by intraneuronal α-synuclein aggregation called Lewy bodies and progressive dopaminergic neurodegeneration. Toll-like receptor (TLR) signaling is a major pathway mediating inflammation. The molecular link how neuroinflammation upregulates neuronal TLRs and induces accumulation of α-synuclein aggregates to drive synucleinopathy remains to be determined. OBJECTIVE: Despite conditioned medium from microglia and TLR agonists were utilized to study their effects on neuronal cells, a transwell co-culture system comprising lipopolysaccharide-activated microglia on top and retinoic acid-differentiated SH-SY5Y cells on bottom more mimicking in vivo neuroinflammation was employed to elucidate the mechanism of activated microglia on neuronal cells. METHODS: Genetic variants of TLRs in PD patients were genotyped as well as assessed the multiplex cytokines, sRAGE and HMGB1. Co-culture system was employed to measure α-synuclein aggregates and neurite shortening by confocal microscope. The expression of TLR2/4 and autophagy flux were detected by western blot and immunofluorescence. RESULTS: PD patients showed higher plasma levels of proinflammatory cytokines and genetic TLR4 variant, c.896 A>G (p. D299G). Elevated proinflammatory cytokines in co-culture medium was also seen. Phosphorylation and aggregation of α-synuclein, shortening of neurite, upregulation of TLR2/4 expression, activation of downstream p38 and JNK, and dampening autophagic flux were seen in SH-SY5Y cells co-cultured with activated microglia. Those were prevented by inhibiting TLR2/4 and p38/JNK signaling. CONCLUSIONS: Activated microglia-derived neuroinflammation induced neuronal TLR2/4-p38/JNK activation to perturb autophagy, causing accumulation of α-synuclein aggregates and neurite shortening. Targeting neuronal TLR2/4 pathway might be a mechanistic-based therapy for neurodegenerative disease, such as PD.